Effects of sintering additives on hot corrosion behavior of γ-Y2Si2O7 ceramics in Na2SO4+V2O5 molten salt. Issue 1 (January 2021) - Fan, Xingyu; Sun, Runjun; Dong, Jie; Wei, Liang; Wang, Qiushi
Abstract: Dense γ-Y2 Si2 O7 ceramics were prepared by moulding and sintering of pure γ-Y2 Si2 O7 powders synthesized by adding various additives. Effects of sintering additives on hot corrosion behavior of γ-Y2 Si2 O7 ceramics in Na2 SO4 + V2 O5 molten salts were systematically investigated. Chemical kinetics of corrosion process was also calculated to illuminate the influence of different additives on chemical stability. Results showed that corrosion reaction started at grain boundary due to the loose microscopic network. When the intercrystalline glass phase was completely etched, the molten salts began to contact Y2 Si2 O7, forming NaY9 Si6 O26 and YVO4 . Compared with Li2 O and MgO, intercrystalline glass phase formed by Al2 O3 additive had the most compact microscopic network structure, leading to the best chemical stability. Apparent activation energy for hot corrosion reaction of γ-Y2 Si2 O7 ceramics in pure Na2 SO4, Na2 SO4 + 5 wt% V2 O5, Na2 SO4 + 10 wt% V2 O5, Na2 SO4 + 15 wt% V2 O5 molten salts was calculated to be 408.16, 373.60, 310.62, and 249.63 kJ/mol, respectively.